La latéralité manuelle préhistorique, les outils et le langage - Natalie Uomini; John Gowlett (Revue de Primatologie)
Why are 90% of people in the world right-handed? How did we become makers and users of such complex tools? Why did human language evolve? We will present archaeological and palaeoanthropological data for right-handedness in hominins. We will present our hypothesis that right-handedness and language are linked through the social and technical skills of our prehistoric ancestors. Language allowed hominins to teach and learn complex tool-making; and complex tool-use influenced the handedness of the species. Technological complexity could be transmitted thanks to the social organisation of hominins, living in larger groups with bigger social networks. Furthermore, the invention of fire would have allowed increased complexity in social relations and tools.